The evolution of consent search law - Kappeler, Victor E. (American journal of criminal justice, 1986)
This study examines the legal issues associated with consent searches conducted by law enforcement officers to gather evidence for criminal prosecutions. Through a review of the available case law relating to consent searches the study examines the requirements of a valid consent to search, the issues associated with these requirements, and the relationship between these requirements and the Fourth Amendment. While the paper focuses on Supreme Court decisions, lower court cases are included to illustrate specific points and examine general trends. The reader is given a general understanding of judicial preferences for procedures to be used when effecting consent searches.